The VULNERABILITY OF SALT FARMER HOUSES IN DONGGOBOLO VILLAGE DUE TO CLIMATE CHANGES - Davit Aldi; Nurhayati; Eka Intan Kumala Putri, (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
This study aims to determine the vulnerability of salt farmer households due to climate change in Donggobolo Village. Weather anomalies resulting from climate change causes floods and droughts which negatively affect household livelihoods. The method for assessing the vulnerability of salt farmer households in this study is the LVI (Livelihood Vulnerability Index) analysis, LVI-IPCC, and descriptive analysis. LVI analysis uses seven components of vulnerability which include climate variability, food, water, health, socio-demographic profile, livelihood strategies, and social networks. The calculation of the overall value of the LVI components shows that the salt farmer household in Donggobolo Village is closer to the scale value for the most vulnerable conditions, with an index value of 0.333. The value of the climate variability component is the dominant value in the LVI, which is equal to 0.759. Based on the grouping of the seven LVI indicators into the IPCC vulnerability components (exposure, adaptive capacity, and sensitivity), the final score is 0.172. The large value of exposure compared to adaptive capacity causes household conditions to be closer to vulnerable conditions.